Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1094/cchem-08-13-0150-r
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rice Flour Blends on Bread Texture and Staling

Abstract: Cereal Chem. 91(2):146-151The effects of blending rice flour with wheat flour on bread texture and staling were investigated with three rice varieties with different amylose contents. For the texture analysis of bread crumb, the compression test, puncture test, and tensile test were performed. A flour blend containing rice flour suppressed the recovery of the crumb after compression. For the puncture test, blends with rice flour increased the distance to penetrate the crumb. The rupture strain measured with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Compressive stress for wheat flour bread and the control bread was similar over 2 days, but it was observed that blending rice flour significantly increased the compressive stress on day 4. This result was consistent with the observation in our previous study (Sasaki et al., ). Yamauchi et al.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Compressive stress for wheat flour bread and the control bread was similar over 2 days, but it was observed that blending rice flour significantly increased the compressive stress on day 4. This result was consistent with the observation in our previous study (Sasaki et al., ). Yamauchi et al.…”
Section: Resultssupporting
confidence: 94%
“…Wheat flour bread had distinctly higher values than the other samples, which agreed with the previous finding of Sasaki et al. (). It was observed that Gu2.0, Xa0.5, 1.0, and 2.0 significantly decreased recovery deformation on days 0, 2, and 4 compared with the control.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There are several studies in literature regarding the application of rice flour in leavened baked products in composite flour mixes with or without incorporating wheat flour (Sasaki, Kohyama, Miyashita, & Okunishi, 2014;Yamauchi et al, 2004). Fari et al (2010) have substituted wheat flour by 30% rice flour for their study and declared that 30% rice flour imparts the best quality attribute in terms of specific volume and crumb structure of the leavened products.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the impact of functional ingredients on the rheological properties of wheat flour dough is critical for successful bread making. In addition, many studies have reported that the textural properties of bread indicate quality and impact its shelf life Ktenioudaki et al 2013;Sasaki et al 2014).…”
Section: Introductionmentioning
confidence: 99%